2006
DOI: 10.1354/vp.43-3-281
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Breed-dependent Differences in Susceptibility to Porcine Circovirus Type-2-associated Disease and Lesions

Abstract: Abstract. Porcine circovirus type 2 (PCV2) has been confirmed as the primary cause of postweaning multisystemic wasting syndrome (PMWS). However, in the field, PMWS is seen only in a small percentage of pigs infected with PCV2. The overall objective of the study reported here was to determine whether host genetic differences in the susceptibility to PCV2-associated disease exist among selected breeds of pigs. This study included Duroc (n 5 23), Landrace (n 5 19), and Large White (n 5 21) pigs. The pigs were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 58 publications
7
80
0
2
Order By: Relevance
“…All pigs were necropsied at 24 wk of age (21 d post PCV2 inoculation). Macroscopic lung lesions, scored from 0 to 100% of the lung affected, and the size of lymph nodes, scored from 0 (normal) to 3 (4 times the normal size), were estimated in a blinded fashion as described previously (Opriessnig et al, 2006a). Lungs were insufflated with fixative.…”
Section: Clinical Evaluation and Necropsymentioning
confidence: 99%
See 1 more Smart Citation
“…All pigs were necropsied at 24 wk of age (21 d post PCV2 inoculation). Macroscopic lung lesions, scored from 0 to 100% of the lung affected, and the size of lymph nodes, scored from 0 (normal) to 3 (4 times the normal size), were estimated in a blinded fashion as described previously (Opriessnig et al, 2006a). Lungs were insufflated with fixative.…”
Section: Clinical Evaluation and Necropsymentioning
confidence: 99%
“…Spanish scientists observed a trend toward genetic susceptibility and PCVAD in field studies involving certain paternal genetic backgrounds (Lopéz-Soria et al, 2004;Sibila et al, 2005). In a controlled trial, Landrace pigs were found to develop more severe microscopic PCV2-associated lesions compared with Large White and Duroc pigs (Opriessnig et al, 2006a). However, a French group was not able to confirm the improvement of PCVAD using selected breeding with Pietrain sires (Rose et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Both these systems display large interindividual variations, partly attributable to genetic background. In pigs, breed-related differences have been observed for basal and stress-induced secretion of cortisol and adenocorticotropic hormone (Dé sauté s et al, 1999;Dé sauté s et al, 2002), acute-phase protein production -E-mail: Elodie.Merlot@rennes.inra.fr (Clapperton et al, 2007), leukocyte blood numbers (Clapperton et al, 2005a), antibody-and cell-mediated immune responses (Joling et al, 1993;Wilkie and Mallard, 1999) and susceptibility to several viruses (Opriessnig et al, 2006;Vincent et al, 2006;Petry et al, 2007). This variability was shown to rely on the additive genetic effects of a few quantitative trait loci (EdforsLilja et al, 2000;Wimmers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As so many aspects of PMWS are as yet unknown, it is difficult to perform deliberate infection experiments and thus difficult to explore the underlying mechanisms. Some breeds have exhibited greater resistance than others (Opriessnig et al, 2006), but again this is mostly circumstantial and difficult to quantify. Therefore although this is a very important disease, at present there is no published evidence of genetic variation in the incidence or severity of PMWS and it is not yet a candidate disease for OG.…”
Section: Opportunities In Livestock Disease Geneticsmentioning
confidence: 99%